PERAN DAN TUGAS RECEPTIONIST PADA PT. SERIM INDONESIA - Nani Nuraini Sarah; Ayu Putri Utari (Universitas Pamulang, 2016)
AbstractReaching a Qualified Receptionist.(This paper is excerpted from the final project report entitled ‘The Role and Tasks of Receptionist in PT Serim Indonesia) It is very usual if we walk-in an office, we are greeted by someone who is known as receptionist. A receptionist is an employee taking an office/administrative support position. The work is usually performed in a waiting area such as a lobby orfront office desk of an organization or business. The title